India’s Soft Power Diplomacy (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Power in International Relations (IR) is defined in relational terms, as the ability of actor A to influence the behavior of actor B to get the outcome he wants. (Nicolas Blarel 2012). That is to say, there is no absolute power. Traditionally, military and economic powers were considered the major factors. However, some other intangible aspects have also been given importance by many strategic thinkers even in the past. The term Soft Power was first used by the eminent IR scholar Joseph Nye in his book "Bound to Lead: The Changing Nature of American Power.” In the book, he identified three dimensions of power; coercion by military force, influence by offering economic incentives and finally the ability to co-opt other states by the nation’s appeal based on its culture and values. The argument is that other states modify their preferences because of their favorable perception of you. They like your story and your narrative. Personally, I have never been a great fan of this concept of Soft Power even though I consider Joseph Nye as a leading IR expert. The problem lies in the definition of the concept. It is very imprecise, to say the least. Is Soft Power a product or a process? I would say it is more the latter than the former. Let me give an example. Normally military power is considered hard and hence looked down upon in the context of Soft Power. However, when it is used for Peacekeeping or disaster relief, it is a humanitarian and welcome activity. Similarly, projection of one’s culture is considered good; however, aggressive projection of a big and historical nation’s culture in smaller countries, particularly in the neighborhood, can be interpreted as cultural imperialism. Hence, the important thing is how one uses the instruments. Soft Power ultimately becomes a process and not a product. Three factors mainly determine the Foreign Policy of a country: its geography, history and capabilities. (David M Malone, Perspectives). Geography is a given. As they say, a country cannot choose its neighbors. Hence, neighborhood policy becomes vital for any nation. Normally, engagements and conflicts are more pronounced with neighbors. History determines the mind sets, outlooks and visions of countries. They also determine some of the linkages with others. Capabilities are what a nation acquires over a period of time. These could be in the military, economic or technological areas. With new capabilities, the Foreign Policy approaches of a country evolves. New interests outside of neighborhood develop. Terms like "extended neighborhood’ and "strategic interests” have become common usages in International Relations.